Records of the U.S. Department of State relating to the internal affairs of Korea, 1945-1949 : Department of State decimal file 895 (1945)
Typescript and holograph correspondence, reports, etc. of the U.S. State Dept. regarding the internal affairs of Korea, 1945-1949. Enclosures include newspaper clippings, etc.